REVITALIZING CULTURE THROUGH NOCTURNAL TOURISM IN YOGYAKARTA: TRENDS, STAKEHOLDERS, AND A CONCEPTUAL FRAMEWORK - Christianto, Jery; Gunawan, Leonardo (JURNAL KEPARIWISATAAN, 2025)
This study explores the evolving phenomenon of nocturnal tourism and its strategic role in revitalizing cultural and artistic expressions, with a specific focus on Yogyakarta, Indonesia. Employing a qualitative literature review and thematic analysis, this paper synthesizes scholarly findings to develop a conceptual framework of nocturnal tourism grounded in cultural preservation, technological integration, and stakeholder engagement. The results reveal that nocturnal tourism in Asia has expanded through diverse cultural practices, nature-based attractions, and tech-enhanced experiences. Yogyakarta demonstrates high potential to adopt these trends by leveraging its rich cultural heritage, night-time traditions, and digitally literate youth. Key findings underscore the importance of community-led initiatives, adaptive spatial planning, and sustainable governance to ensure inclusive and resilient night tourism ecosystems. The study proposes a circular framework built on four pillars: cultural anchoring, tech-enabled sustainability, stakeholder inclusion, and regenerative impact metrics. This conceptual model not only highlights the cultural and socio-economic contributions of nocturnal tourism but also serves as a strategic tool for cultural cities navigating post-pandemic tourism recovery and sustainable urban development.